The spread of rumors in social networks in China - Jing, QinXun (2023)
Rumors are an unavoidable aspect of society. Warren Peterson, Gist, and Noel defined rumor as “an unverifiable account or explanation of events circulating from person to person and pertaining to an object, event, or issue in public concern” (1951). In this regard, a rumor can be viewed as an example of a type of communication that is used in social settings to disseminate information. In spite of this trait, rumors cannot be independently verified from illusory propaganda, gossip, or defamation, which all have specific aims and targets (Zhao et al., 2011). In this definition, rumors are clarified only in terms of their boundaries and connotations, without examining the mechanism by which they spread. It was traditionally word-of-mouth that spread rumors before the emergence of social media. However, now they can be spread through social media networks such as emails, blogging, or through instant messengers.